2007
DOI: 10.1093/cercor/bhm006
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation during Sentence Comprehension among Good and Poor Readers

Abstract: This study sought to increase current understanding of the neuropsychological basis of poor reading ability by using fMRI to examine brain activation during a visual sentence comprehension task among good and poor readers in the third (n = 32) and fifth (n = 35) grades. Reading ability, age, and the combination of both factors made unique contributions to cortical activation. The main finding was of parietotemporal underactivation (less activation than controls) among poor readers at the 2 grade levels. A posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 45 publications
6
86
2
Order By: Relevance
“…Extensive training of problem-solution pairs (e.g., arithmetic facts such as ''3 3 3 5 9'') may finally result in an automatic activation and/or retrieval of the solution upon recognition of the problem. Evidence in favour of this assumption comes from several language studies demonstrating that the angular gyrus is also involved in the mapping between phonological and orthographic units at both, the letter and word level, and in their integration with semantic representations [Booth et al, 2002;Callan et al, 2005;Joubert et al, 2004;Meyler et al, 2007]. Callan et al [2005], for instance, showed that the acquisition of new orthographic-phonological mappings results in increasing angular gyrus activation.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive training of problem-solution pairs (e.g., arithmetic facts such as ''3 3 3 5 9'') may finally result in an automatic activation and/or retrieval of the solution upon recognition of the problem. Evidence in favour of this assumption comes from several language studies demonstrating that the angular gyrus is also involved in the mapping between phonological and orthographic units at both, the letter and word level, and in their integration with semantic representations [Booth et al, 2002;Callan et al, 2005;Joubert et al, 2004;Meyler et al, 2007]. Callan et al [2005], for instance, showed that the acquisition of new orthographic-phonological mappings results in increasing angular gyrus activation.…”
Section: Discussionmentioning
confidence: 99%
“…The question of continuity of function in the brain-behavior relationship remains to be further explored, although initial evidence supports this view (e.g. Hampson et al, 2006;Meyler et al, 2007;Shaywitz et al, 2002). The answer could have relevance for our understanding of the nature of reading problems, and for public policy regarding their identification and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While only a few studies have examined cortical function among poor readers in higher-level reading tasks, evidence is beginning to emerge indicating that underactivation in the parietotemporal and occipito-temporal regions may likewise characterize poor readers when they are reading sentences for comprehension (e.g. Kronbichler et al, 2006;Meyler et al, 2007;Seki et al, 2001). Together, the findings from word-level and sentence-level studies support the view that underfunctioning of these regions represents 0028-3932/$ -see front matter © 2008 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…A study adapting a semantic discrimination task showed that children with good reading skills express increased activation in the left BA 22 (Meyler et al, 2007). In another study on children and adults, high word generation performance is predominantly characterized by activation in the right frontal cortex and in medial cortical areas (Brown et al, 2005).…”
Section: Language Ability In Adultsmentioning
confidence: 97%
“…The review suggests that there is a mainly left-lateralized network, involving frontoparietal regions, activated by tasks tapping intelligence and reasoning. The functional correlates of this model may be explained by the neural efficiency hypothesis of intelligence, which states that less activation in involved neural networks is correlated with increased cognitive performance (Haier et al, 1988;Neubauer & Fink, 2009;Brown et al, 2005;Meyler et al, 2007).…”
Section: Language Ability In Adultsmentioning
confidence: 99%